METHODS OF ORGANIZING PRACTICAL TRAINING IN SERVICE SERVICE IN TECHNOLOGY CLASSES - Ortikova Ozoda (American Journals, 2023)
In this article, ideas were put forward about the methods of organizing practical training in service service in Technalogy classes, about the effective organization of Technology classes.
Keywords: technology, team, need, training, public.